Development of Microsoft Excel-Based Templates to Analyze Skills Assessment (Project and Performance) of Elementary School Students - Jejen Jaenudin; Devi Afriyuni Yonanda; Eka Nurhidayat (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
Assessment is a fundamental component of the learning process, particularly in elementary education, where students’ skills must be measured authentically through project and performance assessment. However, teachers often face difficulties in managing, analyzing, and reporting assessment data due to manual processing, limited time, and heavy administrative workload. This study aimed to develop a Microsoft Excel–based template to analyze students’ skill assessment and examine its feasibility and usefulness in elementary school contexts. The research used a research and development approach at Sukawana Public Elementary School, Majalengka Regency. Data were collected through interviews, observations, questionnaires, and documentation involving classroom teachers as users. The development process included needs analysis, design, development, and limited trials. Findings showed the template integrated indicators, rubrics, automated scoring, and data recap systematically. Teachers reported it was easy to use, reduced errors, and improved efficiency. The template is a practical solution, and further research should test broader implementation and online integration.